PENINGKATAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MELALUI MODIFIKASI MEDIA KARDUS PADA SISWA KELAS V SDN MERTAK WARENG: PENELITIAN TINDAKAN KELAS - Damara, Dani; Muhammad Salabi; Kokom Supriyatnak (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
This study aimed to improve students' long jump learning outcomes through the use of modified cardboard-based learning media in fifth-grade students of SDN Mertak Wareng. The study employed Classroom Action Research conducted in two cycles, with each cycle comprising planning, action, observation, and reflection. The research subjects consisted of 20 students. Data were collected through performance tests and classroom observation sheets, and analyzed descriptively using mean scores and classical mastery percentages. The findings demonstrated a consistent improvement in students' learning outcomes across cycles. The mean score increased from 64 in the pre-action stage to 74 in Cycle I and 84 in Cycle II. Classical mastery also improved from 55% to 80% and finally 90%. These results indicate that modified cardboard media can create a safer, more concrete, and more engaging learning environment, thereby contributing to improved long jump learning outcomes in elementary school physical education. Therefore, the use of simple modified media is recommended as an alternative instructional strategy in PJOK learning, particularly for basic athletic skills.